Bio-inspired Nickel Oxides Nanoscale Synthesis by using Peel of Citrus Sinensis. (2020) - Fall, A.; Mayedwa, N.; Bucher, R.; Ngom, B. D.; Maaza, M.
Abstract: This contribution provides the synthesis and characterization of nickel oxide nanoparticles (NiO NPs) which were prepared by green synthesis method using natural extract oranges peel skin (Peel Citrus Sinensis) as an effective bio-oxidizing/bio-reducing agent. The effect of different calcination temperatures on the size of the NiO NPs was investigated. The prepared nanoparticles were characterized by various techniques such as X-rays diffraction (XRD) results indicated that all the samples have a face-centered cubic (FCC) structure and confirmed the presence of high degree of crystallinity nature NiO NPs. The functional group composition of NiO NPs were investigated by using attenuated total reflection-Fourier transform infrared (ART-FTIR), Photoluminescence (PL), and Scanning electron microscopy (SEM).